The Isolation of Xanthones from Trunk Latex of Garcinia mangostana Linn. and Their Antimicrobial Activities - Vivi Anggia; Amri Bakhtiar; Dayar Arbain (Indonesian Journal of Chemistry, 2015)
ɑ-Mangostin (1), β-mangostin (2) and gartanin (3) have been isolated from the trunk latex of Garcinia mangostana Linn. and investigated for their antimicrobial activities against Bacillus subtilis, Enterococcus faecalis, Micrococcus luteus, Salmonella typhosa, Staphylococcus epidermidis, Streptococcus mutans and Vibrio cholerae. The significant antibacterial activity showed by α-mangostin (1) against Bacillus subtilis, Enterococcus faecalis. Staphylococcus epidermidis and Vibrio cholerae, but all compounds showed no activity to inhibit the growth of Micrococcus luteus and Streptococcus mutans.